The impact of Sports Activities on Economic Survival, Social Life of Women, and What do Big Data Analysis reveals about Social Life of Sports Women - Li Shidong; Tsung-Hsien Kuo; Misbah ul Islam; Muhammad Talha; Showkat Ahmad Lone; Siao-Yun Wei (Revista de Psicología del Deporte (Journal of Sport Psychology), 2021)
Economic Survival and Social Support in Sports activities is a multifaceted area of research interest. Active participation of women in sports activities has a significant contribution to the growth and success of the sports industry. This article seeks to discuss the impact of sports activities on sportswomen's economic survival and social life. This is done using questionnaire themed around issues such lack of availability of time, limitations of knowledge, family-related and financial difficulties, and nature of activities, all of which can potentially impact the social life of sportswomen. The study shows that economic survival is a significant part of sport's activities as well as the social life of sportswomen. Economic survival supports the social life of sportswomen. The current article highlights the findings from big data analysis pertaining to the social life of sportswomen. The paper uses Big Data Analysis to examine the social life of sportswomen. However, BDA is a complex process resulting from data sources' diverse and unstructured nature. Big Data Analysis (BDA) is critical in the sports field, as it covers the data at the macro-level (such as the national sports industry, teams, and individuals). It was analyzed using the AMOS 23v and SPSS 26v after being collected from female sports players belonging to a geographically diverse region. The study found that there is a significant association between sports activities, economic survival, and the social life of sportswomen.